Epilepsy as a Network Disorder (2): What can we learn from other network disorders such as dementia and schizophrenia, and what are the implications for translational research? - Scharfman, Helen E.; Kanner, Andres M.; Friedman, Alon; Blümcke, Ingmar; Crocker, Candice E.; Cendes, Fernando; Diaz-Arrastia, Ramon; Foerstl, Hans; Fenton, Andre A.; Grace, Anthony A.; Palop, Jorge; Morrison, Jason; et al. (Epilepsy and Behavior, 2018)
There is common agreement that many disorders of the central nervous system are 'complex', that is, there are many potential factors that influence the development of the disease, underlying mechanisms, and successful treatment. Most of these disorders, unfortunately, have no cure at the present time, and therapeutic strategies often have debilitating side effects. Interestingly, some of the 'complexities' of one disorder are found in another, and the similarities are often network defects. It seems likely that more discussions of these commonalities could advance our understanding and, therefore, have clinical implications or translational impact. With this in mind, the Fourth International Halifax Epilepsy Conference and Retreat was held as described in the prior paper, and this companion paper focuses on the second half of the meeting. Leaders in various subspecialties of epilepsy research were asked to address aging and dementia or psychosis in people with epilepsy (PWE). Commonalities between autism, depression, aging and dementia, psychosis, and epilepsy were the focus of the presentations and discussion. In the last session, additional experts commented on new conceptualization of translational epilepsy research efforts. Here, the presentations are reviewed, and salient points are highlighted.
EVALuna2:34600